Especies nativas del matorral espinoso del noreste mexicano con posibilidades de aprovechamiento industrial - Rechy Carvajal, María de los Ángeles; Roth Rechy, Emil von (Instituto de Ecología, A.C., 2016)
Brushwood species have been spurned traditionally, their use being limited to the production of fences, firewood and charcoal. This paper presents research results on the microscopical anatomy and physical-mechanical properties of four brushwood species typically found in Northeastern Mexico, with the purpose of expanding the possibility of their commercial use. The species are barreta (Helietta parvifolia (Gray ex Hemsl.) Benth), canelon (Melia azedarach L.), ebony (Ebenopsis ebano ( Berl. ) Barneby & Grimes), and tenaza (Havardia pallens ( Benth.) Britt. & Rose). The physical-mechanical properties determined are density, percentage of shrinkage and swelling, modulus of elasticity, and flexural strength. Test results for baretta prove that its wood is heavy, hard, easy to dry, and flexible with little shrinkage during the drying process. Canelon (also known as chinaberry or umbrella tree) is characterized by having a higher density compared to other species. This wood has wide annual growth rings, being easy to dry and work with, and resistant to insect attack. Ebony exhibits a heavy wood that it is only possible to work while green or through special machinery when dry. Ebony's heartwood has a low susceptibility to insect infestations. Shrinkage is similar to that of pine wood (sometimes slightly lower), it is easy to dry, very flexible when wet, however not very resistant to insect infestations.